USM STRENGTHENS PARTNERSHIP WITH AMER SPORTS MALAYSIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 June 2015 – Universiti Sains Malaysia (USM) through the Sports and Recreation Centre (PSR) continues to strengthen its amicable partnership with Amer Sports Malaysia Sdn Bhd by extending the memorandum of understanding (MoU) on the sponsorship of sports attire and equipment bearing the “Wilson” brand name until 2018.